Experimental and numerical simulation of lightning damage development on composites with/without a carbon-based protection layer. (15th March 2021) - Duongthipthewa, Anchalee; Lu, Mingyu; Du, Kui; Ye, Lin; Zhou, Limin
Abstract: We analyzed a three-dimensional thermal-electrical coupled model based on COMSOL to characterize the thermal damage response of a woven carbon fiber reinforced polymer (CFRP) composite with and without a lightning strike protection (LSP) system. Fuzzy fiber (FF) fabric serving as a carbon-based protection layer was attached to the outermost ply of the CFRP composite to fabricate a fuzzy fiber reinforced polymer (FFRP) composite. CFRP and FFRP composites with temperature-dependent properties were inspected to predict lightning-induced damage resulting from a 20- and 40-kA peak current for 100 μs. The predicted area of thermal damage and the appearance of the composite surface agreed fairly well with post-lightning damage observed from experiments, thus demonstrating the credibility of the numerical model. LSP characteristics were evaluated for a range of CFRP composite properties in the outermost layer by enhancing the functional conductivity of the top layer in the in-plane and out-of-plane directions. The irreversible thermal damage region in the in-plane and thickness directions was dramatically mitigated by enhanced electrical conductivity, whereas a slight matrix decomposition damage change was observed by varying the thermal conductivity. Due to the increased electrical conductivity and integration of the lightweight FF carbon-based protection layer into the uppermost composite layer, the depth and area of damage can be limited by decreasing the thermal damage penetration through the underlying composites. These results reveal that a highly conductive FF layer may serve as a lightweight and effective anti-lightning strike layer for protecting the underlying composite.